Hesychast Idea of Deification and Its Representation in Spiritual Epistolary of Russian Orthodox Monasticism of 20 Century - A. N. Smolina (Научный диалог, 2019)
The features of representation in the spiritual epistolary of Russian writers-monks of the idea of deification (theosis), the statement of which is associated with the development in the Orthodox culture of the ancient religious and philosophical teachings of Hesychasm, are considered. Presenting the Hesychast ideosphere, the author focuses on the content of the idea of deification and its representative images and linguistic units. As the main images the images of Jesus Christ and Christlike people (saints) are distinguished. The most important for the realization of the idea of deification are theonyms (God, Lord, heavenly Father, Holy Spirit, Jesus Christ, Son of God, Savior, God-man, God-child) and hagio-anthroponyms (St. Ephraim the Syrian, St. Isaac the Syrian, St. Demetrius, St. Ignatius, St. Theophanes, etc.). The group of representatives of the patristic idea of deification also includes linguistic units related to the corpus of Orthodox vocabulary of spiritual and moral content (Kingdom(s) of God, deification, transformation, rebirth, ascension, love, reverence, God-thinking, knowledge of God, piety, sacrifice, etc.), and language units denoting religious texts (Gospel, Apostle, New Testament, Paterikon, Jesus prayer, life, etc.). In addition, intertexts that contribute to the realization of the idea of deification are revealed. The role of the idea of deification in the life of Orthodox Christians, in particular monastics, its importance in the spiritual and moral development of believers is considered separately.